Effectiveness of pen aquaculture in enhancing small scale fisheries production and conservation in a wetland of India - Karnatak, Gunjan; Das, Basanta Kumar; Parida, Pranaya; Roy, Aparna; Das, Archan Kanti; Lianthuamluaia, Lianthuamluaia; Ekka, Anjana; Chakraborty, Sangeeta; Mondal, Kausik; Debnath, Sanjeet (Frontiers in Sustainable Food Systems, 2025)
The present study deals with stakeholder-driven implementation of pen culture for raising of fish seed for Culture-based fisheries (CBF) in Chamta, a floodplain wetland, in Gangetic plains through polyculture of Indian Major Carps (IMCs) Labeo catla, Labeo rohita and Cirrhinus mrigala with Small Indigenous Fishes (SIFs) Labeo bata, Systomus sarana and grass carp, Ctenopharyngodon idella in co-management mode. In the first polyculture trial IMCs and minor carps were cultured in 4 High Density Poly Ethylene (HDPE) pens (0.1 ha each) at a stocking density of 25 Nos. m−3 in equal numbers for 90 days. In the second polyculture trial IMCs were cultured with grass carp at a density of 25 Nos. m−3 in 4 HDPE pens in the ratio of 1:1:1:2 for 90 days. The same set of pens was utilized for both trials during different times of the year. Net yield of 682.3 ± 20.6 kg and 413.9 ± 21.7 kg per pen was achieved through polyculture of IMCs and SIFs and polyculture and for IMCs and grass carp, respectively. The survival percentage varied with species and culture period with overall survival of 77 (IMCs + minor carps) to 85% (IMCs + grass carp). Polyculture was economically feasible with a BC ratio of 2.01 for IMC and SIFs and 1.88 for IMC and grass carp. All the seeds produced in the pens were released to the wetland as input for CBF. The study indicated the potential of grass carp fishery in macrophyte-infested wetland. The species could attain 1.5–2 kg in 6 months and up to 3–3.5 kg weight within 1 year, utilizing macrophyte resources of the wetland. SIFs S. sarana and L. bata were observed to attain maturity in pens. The study indicated pen as an economically feasible technology to boost CBF in the wetland. The cultivation of SIFs through pen culture and CBF can enhance their production while alleviating pressure on their natural populations. Integrating pen culture using diversified species will promote sustainable fisheries management in these floodplain wetlands.